DIVERSION CHANNEL PLANNING FOR COAL MINING ACTIVITIES IN TANAH BUMBU DISTRICT, SOUTH KALIMANTAN - Aulia Rahman, Farras
Satui Mine is one of the mines that has been operating since the establishment of PT Arutmin Indonesia. Mining activities at Satui Mine continue to be carried out until now, but the original river flow at PIT Rama is indicated to interfere with mining activities. The original river flow also has medium-high permeability, so it is necessary to move the river channel to an area with low permeability that has the potential for water infiltration and avoid erosion and sedimentation. The research is intended to analyze and design the right channel dimensions to safely accommodate the new river flow plan discharge using HEC - HMS and HEC - RAS modeling with the Stable Channel concept. Features in HEC-RAS are used to determine the hydrograph conditions at the outlet. The results showed that to accommodate a 50-year return period flood discharge of 83.70 m3/s, the optimal new channel recommendation is a trapezoidal shape with a channel bottom width of 6.60 m, a channel top width of 26.42 m, a cross-sectional area of 54.53 m2, a channel depth of 3.30 m, a manning roughness of 0.023 (soil), a channel embankment slope of 3, and a channel slope of 0.013. Based on the results of the planning carried out, the cost budget plan (RAB) of the Diversion Channel is IDR 63,041,000,000.00.